2017
DOI: 10.1002/ejlt.201700104
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide‐rich hydrolysate from Saccharomyces cerevisiae (LipiGo®) increases fatty acid and neutral sterol excretion in guinea pigs fed with hypercholesterolemic diets

Abstract: This study aimed to evaluate the hypolipidemic properties of a polysaccharide‐rich hydrolysate from Saccharomyces cerevisiae comprising β‐glucan‐chitin‐chitosan (BCC). Guinea pigs (n = 8 per group) were fed high‐fat and hypercholesterolemic diets (17 g/100 g of fat, 0.2 g/100 g of cholesterol), containing 12 g/100 g of either cellulose (CEL) as negative control, oat bran as a source of β‐glucan (BOB), or BCC. Food intake and body weight were monitored for 4 weeks and fatty acid (FA), neutral sterol (NS), and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…This led to the postulation that this complex may not be the best choice as an effective BAS but rather its hypocholesterolemic effect is based on its interactions with exogenous cholesterol; the excretion signaled the liver to increase LDL uptake, thereby reducing plasma concentrations of the LDL. 176 The BA scavenging activities were also reported by Huang et al 177 and Cheng et al 178 for the functionalized chitosan (CS) obtained from squid pens. The former study modified the extracted chitosan via carboxylation to yield N-carboxyethylated derivatives (N-CECSs) having different degrees of substitution (DSs).…”
Section: ■ Cellulose and Derivatives As The Bassmentioning
confidence: 64%
See 2 more Smart Citations
“…This led to the postulation that this complex may not be the best choice as an effective BAS but rather its hypocholesterolemic effect is based on its interactions with exogenous cholesterol; the excretion signaled the liver to increase LDL uptake, thereby reducing plasma concentrations of the LDL. 176 The BA scavenging activities were also reported by Huang et al 177 and Cheng et al 178 for the functionalized chitosan (CS) obtained from squid pens. The former study modified the extracted chitosan via carboxylation to yield N-carboxyethylated derivatives (N-CECSs) having different degrees of substitution (DSs).…”
Section: ■ Cellulose and Derivatives As The Bassmentioning
confidence: 64%
“…For the in vitro adsorption test, the hydrophobic chitin (50 mg/mL) displayed better binding with BAs due to the hydrophobic interactions, leading to the aggregation of BAs/BSs on the surfaces. 175 Santas et al 176 analyzed the BA binding propensity of LipiGO in guinea pigs, where the LipiGO (30−60 wt % βglucan and 1−3 wt % N-acetyl-glucosamine) is a polysaccharide-rich hydrolysate composed of β-glucan-chitinchitosan (BCC) derived from the cell wall of Baker's yeast, Saccharomyces cerevisiae. Guinea pigs were used in the lipid metabolic study, and they were fed a high-fat diet to reduce the error associated with total fat absorbed calculations.…”
Section: ■ Cellulose and Derivatives As The Bassmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, it has been reported that yeast culture ( Saccharomyces cerevisiae ) or yeast‐derived additives presented positive impacts on growth performance, carcass weight, leg yield and meat quality of pigs and broilers 11,12 . In addition, research on ruminants and rodents has demonstrated that the addition of live yeast or polysaccharide‐rich hydrolysate from Saccharomyces cerevisiae in the diet decreased low‐density lipoprotein cholesterol (LDL‐C), total cholesterol (TC) and blood urea nitrogen in serum, thus regulating serum metabolism in the body 13,14 . Moreover, relevant research studies on aquatic animals have indicated that fish fed with yeast hydrolysate showed enhanced activities of superoxide dismutase (SOD), glutathione peroxidase (GSH‐Px) and catalase (CAT), but decreased concentration of malonaldehyde (MDA) in the liver 5,10 .…”
Section: Introductionmentioning
confidence: 99%
“…11,12 In addition, research on ruminants and rodents has demonstrated that the addition of live yeast or polysaccharide-rich hydrolysate from Saccharomyces cerevisiae in the diet decreased low-density lipoprotein cholesterol (LDL-C), total cholesterol (TC) and blood urea nitrogen in serum, thus regulating serum metabolism in the body. 13,14 Moreover, relevant research studies on aquatic animals have indicated that fish fed with yeast hydrolysate showed enhanced activities of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and catalase (CAT), but decreased concentration of malonaldehyde (MDA) in the liver. 5,10 Park et al 15 indicated that yeast hydrolysate (YH) improved egg production and quality as well as nutrient digestibility of laying hens, and Fu et al 16 showed that YH enhanced antioxidant capacity in serum as well as the counts of beneficial bacteria in cecum of growingfinishing pigs.…”
Section: Introductionmentioning
confidence: 99%